2016
DOI: 10.1039/c5ra23447f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a carboxymethylated guar gum grafted polyethyleneimine copolymer as an efficient gene delivery vehicle

Abstract: In the present study, a carboxymethylated guar gum-grafted-polyethyleneimine copolymer (CMGG-g-PEI) was synthesized and characterized by FT-IR, 1H NMR, XRD and zeta potential analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…A carboxymethylated guar gum-grafted-polyethyleneimine copolymer (CMGG-g-PEI) was reported as an effective gene carrier in another study by Jana et al [ 168 ]. The less toxic profile of CMGG-g-PEI was revealed by cytotoxicity and blood compatibility experiments.…”
Section: Applicationsmentioning
confidence: 99%
“…A carboxymethylated guar gum-grafted-polyethyleneimine copolymer (CMGG-g-PEI) was reported as an effective gene carrier in another study by Jana et al [ 168 ]. The less toxic profile of CMGG-g-PEI was revealed by cytotoxicity and blood compatibility experiments.…”
Section: Applicationsmentioning
confidence: 99%
“…Although b-PEI has shown to be an excellent transfection vector, it has some limitations, among which are its cytotoxicity, low biodegradability, and low specificity, which gives rise to non-specific interactions with normal cells or blood components at the in vivo level, and this causes a decrease in the half-life of the PEI / DNA polyplexes in the bloodstream [ 20 ]. In order to overcome these limitations, some studies have reported the modification of b-PEI through functionalization with synthetic and natural polymers [ 21 ], for example, polysaccharides [ 22 , 23 , 24 ], poly (ethylene glycol) (PEG), poly ( ε -caprolactone), and poly (l-lactide) (PLLA). In the case of polysaccharides, they have attracted the interest of many researchers in gene therapy due to their advantages, such as biocompatibility, biodegradability, low toxicity, and various modification strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of polysaccharides, they have attracted the interest of many researchers in gene therapy due to their advantages, such as biocompatibility, biodegradability, low toxicity, and various modification strategies. Among the polysaccharides that have been used to carry out this modification are chitosan, cellulose, and natural gums [ 22 , 24 , 25 ]. Several strategies have been adopted to reduce polyethyleneimine (PEI) toxicity as the nucleic acid carrier [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers attempted modification of guar gum [33] like carboxymethylation [5,34,35], methylation [36], cationic guar gum [4] etc. In cationic guar gum (CGG) the hydroxyl groups are replaced with trimethyl ammonium groups.…”
Section: Introductionmentioning
confidence: 99%